2021
DOI: 10.3390/foods11010033
|View full text |Cite
|
Sign up to set email alerts
|

A FT-NIR Process Analytical Technology Approach for Milk Renneting Control

Abstract: The study proposes a process analytical technology (PAT) approach for the control of milk coagulation through near infrared spectroscopy (NIRS), computing multivariate statistical process control (MSPC) charts, based on principal component analysis (PCA). Reconstituted skimmed milk and commercial pasteurized skimmed milk were mixed at two different ratios (60:40 and 40:60). Each mix ratio was prepared in six replicates and used for coagulation trials, monitored by fundamental rheology, as a reference method, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Fourier Transformed (FT)-NIR has become popular for online and at-line process control in the dairy industry with many practical applications such as the determination of moisture, protein, fat and lactic acid ( 41 , 42 ). FT-NIR has also been used by Grassi et al ( 43 ) to monitor milk coagulation after the addition of rennet. The study found that an FT-NIR probe could successfully monitor coagulation in real time when combined with multivariate curve resolution and alternating least squares for data analysis.…”
Section: Spectroscopic Technologies and Their Usage In The Dairy Indu...mentioning
confidence: 99%
“…Fourier Transformed (FT)-NIR has become popular for online and at-line process control in the dairy industry with many practical applications such as the determination of moisture, protein, fat and lactic acid ( 41 , 42 ). FT-NIR has also been used by Grassi et al ( 43 ) to monitor milk coagulation after the addition of rennet. The study found that an FT-NIR probe could successfully monitor coagulation in real time when combined with multivariate curve resolution and alternating least squares for data analysis.…”
Section: Spectroscopic Technologies and Their Usage In The Dairy Indu...mentioning
confidence: 99%
“…For this reason, different types of sensors that can provide timely information are becoming more and more used for on-line quality probing from raw materials to the semi-finished and final products. It has been widely demonstrated that NIR spectroscopy has a powerful potential in monitoring food production processes [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], due to its ability to detect both chemical and physical changes in the samples. To cite a few applications: NIR has been used for process monitoring in the dairy industry, from the prediction of raw milk composition to milk coagulation in cheese production and yogurt fermentation [ 11 ]; the fermentation processes in the wine and brewery industries; and the powdered ingredients mixing stage in different food matrices [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the calibration set was chosen by using the Kennard-Stone algorithm and next, all method performances were compared by evaluating the validation sample set at multiple process stages (from the loading dock to the process line), which is a critical part of PAT initiatives. [7][8][9][10] Handheld, portable, and miniaturised NIR and Raman instruments are especially suited for PAT applications. In fact, their portability and versatility make them suitable for monitoring the pharmaceutical process.…”
Section: Introductionmentioning
confidence: 99%